Respuesta :

Considering the given functions in the graph, we have that:

  • (f + g)(3) = 4.
  • (f - g)(1) = -2.

How to find (f + g)(3) looking at the graph?

We look at the graph, and find f(3) and g(3), then add them. Hence:

  • g(3) = 4.
  • f(3) = 0.

Then the addition is:

(f + g)(3) = f(3) + g(3) = 0 + 4 = 4.

As for (f - g)(1):

Same logic, at the graph we have that:

  • f(1) = -1.
  • g(1) = 1.

Hence:

(f - g)(1) = f(1) - g(1) = -1 - 1 = -2.

More can be learned about functions at https://brainly.com/question/25950034

#SPJ1